2009
DOI: 10.1038/modpathol.2009.74
|View full text |Cite
|
Sign up to set email alerts
|

Differential protein immunoexpression profiles in appendiceal mucinous neoplasms: a special reference to classification and predictive factors

Abstract: Appendiceal mucinous neoplasms have been the focus of considerable debate in recent years. We histologically classified 70 appendiceal mucinous neoplasms into three categories: 32 mucinous adenoma, 23 mucinous neoplasm of uncertain malignant potential, and 15 mucinous adenocarcinomas. Immunohistochemistry was performed for 24 proteins in different functional categories, specifically, oncogenic proteins (bcl-2, b-catenin, CEA, C-erbB2, c-kit, Cox-2, Cyclin D1, EGFR, Ki-67, NF-jB, VEGF), tumor suppressors (E-cad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…Moreover, we adopted the term 'appendiceal mucinous neoplasm of uncertain malignant potential' from Carr et al [2] , and followed the criteria revisited by Pai et al [4] . We strictly defined 'appendiceal mucinous neoplasm of uncertain malignant potential' in the present study as follows: under the condition of lost muscularis mucosae or undiscerned individual layers of the appendix (accordingly, 'undetermined invasion'), appendiceal mucinous neoplasms display a bland cytoarchitecture, but the features show (1) epithelium pushing deeply into underlying tissue, (2) a cystic gland-like structure in the appendiceal wall or (3) uncertainty of complete excision, such as a positive proximal margin or extensive mucin on the appendiceal serosa [6] .…”
mentioning
confidence: 76%
See 4 more Smart Citations
“…Moreover, we adopted the term 'appendiceal mucinous neoplasm of uncertain malignant potential' from Carr et al [2] , and followed the criteria revisited by Pai et al [4] . We strictly defined 'appendiceal mucinous neoplasm of uncertain malignant potential' in the present study as follows: under the condition of lost muscularis mucosae or undiscerned individual layers of the appendix (accordingly, 'undetermined invasion'), appendiceal mucinous neoplasms display a bland cytoarchitecture, but the features show (1) epithelium pushing deeply into underlying tissue, (2) a cystic gland-like structure in the appendiceal wall or (3) uncertainty of complete excision, such as a positive proximal margin or extensive mucin on the appendiceal serosa [6] .…”
mentioning
confidence: 76%
“…According to a recent study, leptin contributes to mucin production in colonic epithelial cells, and a leptininduced increment of mucins, such as MUC2, MUC5AC and MUC4, has been reported [11,12] . We had previously reported that MUC2 and MUC5AC were related to the malignant behaviour of appendiceal mucinous neoplasms [6] . Recently, leptin was identified as multifunctional, i.e., it not only controls food intake and energy balance [13] , but it also regulates carcinogenesis [14][15][16] and inflammatory processes [17] .…”
mentioning
confidence: 96%
See 3 more Smart Citations